Between the reasonable and the particular: Deflating autonomy in the legal regulation of informed consent to medical treatment - Dunn, M; Fulford, K; Herring, J; Handa, A (Springer Verlag, 2018)
The law of informed consent to medical treatment has recently been extensively overhauled in England. The 2015 Montgomery judgment has done away with the long-held position that the information to be disclosed by doctors when obtaining valid consent from patients should be determined on the basis of what a reasonable body of medical opinion agree ought to be disclosed in the circumstances. The UK Supreme Court concluded that the information that is material to a patient’s decision should instead be judged by reference to a new two-limbed test founded on the notions of the ‘reasonable person’ and the ‘particular patient’. The rationale outlined in Montgomery for this new test of materiality, and academic comment on the ruling’s significance, has focused on the central ethical importance that the law now (rightfully) accords to respect for patient autonomy in the process of obtaining consent from patients. In this paper, we dispute the claim that the new test of materiality articulated in Montgomery equates with respect for autonomy being given primacy in re-shaping the development of the law in this area. We also defend this position, arguing that our revised interpretation of Montgomery’s significance does not equate with a failure by the courts to give due legal consideration to what is owed to patients as autonomous decision-makers in the consent process. Instead, Montgomery correctly implies that doctors are ethically (and legally) obliged to attend to a number of relevant ethical considerations in framing decisions about consent to treatment, which include subtle interpretations of the values of autonomy and well-being. Doctors should give appropriate consideration to how these values are fleshed out and balanced in context in order to specify precisely what information ought to be disclosed to a patient as a requirement of obtaining consent, and as a core component of shared decision-making within medical encounters more generally.